Expression of obestatin and ghrelin in papillary thyroid carcinoma - Karaoglu, Aziz; Aydin, Suleyman; Dagli, Adile F.; Cummings, David E.; Ozercan, Ibrahim H.; Canatan, Halit; Ozkan, Yusuf (Springer, 2009)
Ghrelin and obestatin are two peptide hormones with opposing roles in the control of appetite: orexigenic and anorexigenic, respectively. Loss of appetite is a common, serious complication of many forms of malignancy. The goals of this study were to investigate: (i) whether there are differences in ghrelin and obestatin peptide expression in thyroid tissues from a series of papillary carcinoma cases and normal controls, and (ii) whether there are correlations between tissue ghrelin and obestatin levels in series of papillary carcinoma cases and normal controls. Immunohistochemical analysis showed that in sections of benign human thyroid tissue, anti-ghrelin antibody reacted with intense staining in colloid-filled follicles. In benign thyroid tissues, colloids displayed plentiful dispersion in comparison with papillary microcarcinomas, whereas colloids in malignant thyroid tissues were uncommon. We found markedly lower tissue ghrelin levels in thyroid tissue of patients with papillary carcinomas, compared with normal thyroid tissues (P = 0.001). Immunohistochemical analysis also showed that obestatin in papillary carcinoma stained positively to various degrees. Obestatin tissue levels in papillary carcinomas tended to be slightly higher than those in normal thyroid tissue, but this was not statistically significant (P = 0.29). We also report that thyroid tissue of patients with Hashimoto's thyroiditis produced ghrelin and obestatin at similar levels as in normal thyroid tissue, even though colloid in Hashimoto's disease is scarce. We conclude that depressed expression of ghrelin, but not obestatin, is specific to papillary carcinoma, and this difference might constitute a diagnostic tool to differentiate papillary carcinoma from normal thyroid tissue. We currently do not know how these peptides are regulated and what factors are involved in papillary carcinoma, which inhibit the expression of ghrelin but not obestatin. This issue warrants further studies.
Keywords: Papillary thyroid carcinoma; Obestatin; Ghrelin